Evaluation of the ZrO2/Al2O3 system as catalysts in the catalytic transfer hydrogenation of furfural to obtain furfuryl alcohol - Jiménez Gómez, Carmen Pilar; Viar-Antuñano, N.; Cecilia-Buenestado, Juan Antonio; Moreno-Tost, Ramón; Mérida-Robles, Josefa María; Requies, Jesús M.; Maireles-Torres, Pedro Jesús (Elsevier, 2021)
ZrO2, Al2O3 and ZrO2/Al2O3 with different Zr/Al molar ratio, have been synthesized by coprecipitation and subsequent calcination. The resulting catalysts were characterized by X-ray diffraction, transmission electron microscopy, N2 adsorption-desorption at -196 ◦C, CO2-thermoprogrammed desorption, NH3-thermoprogrammed desorption and X-ray photoelectron spectroscopy. Then, the catalysts were evaluated in the Meenwein-Ponndorf-Verley reduction of furfural (FUR) using 2-propanol as sacrificing alcohol. The catalyst with a Zr/Al molar ratio of 1, Zr5Al5, reached the highest conversion value at shorter reaction times, attaining a FUR conversion of 95 % with a yield of furfuryl alcohol (FOL) above 90 % after 5 h of reaction at 130 ◦C, due to its greater amount of acid sites, as well as higher specific surface area and pore volume.
Keywords: Catálisis heterogénea; ZrO2/Al2O3 catalysts; Heterogeneous catalysts; Furfural; Furfuryl alcohol; Catalytic transfer hydrogenation